Peran Orang Tua Dalam Pengenalan Pendidikan Seks Bagi Anak Usia Dini - A.J. Pauweni, Apriyanto; loni, ainunloni; R. Yakob, Ratih (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2022)
The Department of Population Control, Family Planning, Women's Empowerment and child Protection (DPPKBP3A) of the Blitar Regency noted that during January to October 2021 there were around 37 cases of sexual violence against children. Where 20 of them are female victims. Early childhood sex education aims to provide knowledge to children about their nature as humans who physical differences between men and women or are called sex classifications. Sexual education is a lesson given to someone to find out various information related to the development of sexuality. In general, sexual education is clear and correct information related to sexuality, which includes the process of conception, pregnancy to birth, sexual behavior, sexual relations, and aspects of health, psychology and society. sex education given to children from an early age is a form of effort to provide correct knowledge to children about sex itself. The number of cases of sexual violence against children is triggered by the lack of awareness of parents in providing education and supervision about sex.